Interactive UTAR WBLE portal - Lee, Chuan How (2019)

(untitled)
An Electronic Document Management System (EDMS) was developed called Interactive UTAR Wble Portal. This is an extension system from official web-based learning platform called Web-Based Learning Environment (WBLE). This system is adopted by mobile platform, Android, in order to provide the ease of document access. The motivation of this project is to overcome the problem of students who is unable to manage their study especially during peak semester. Therefore, mobile platform is the way to provide the accessibility. Furthermore, the features of this system were emphasized on the modification on PDF files and files reading history. This system provides the ability of PDF file modification to students, students are able to add some notes on the files but not editing original file content. To perform the function, custom PDF viewer is adopted to handle the file process. Next, to handle the user history, a famous cloud database was adopted to this system. The cloud database named Firebase, managed by Google. The type of database used in this project is Cloud Firestore, it supports fast querying than SQL due to the database structure is much different and SQL, also Cloud Firestore is a non-SQL database. Therefore, new data structure of storing user data is designed and developed in order to become compatible to the database.